2021
DOI: 10.3390/ijerph18010306
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep during the First Peak of the SARS-CoV-2 Pandemic: A Cross-Sectional Study

Abstract: The restrictions enacted during lockdown to limit the spread of the novel coronavirus (SARS-CoV-2) have led to changes in people’s lifestyle habits. In Italy, these restrictions have dramatically changed the way people work and spend their leisure time, also with repercussions on diet and physical activity. An anonymous survey was disseminated via websites and social media to a convenience sample of the Italian population during and immediately after the first lockdown (10 March–18 May 2020). Data collected on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…Moreover, the members of the police force were more likely to report poor sleep quality than volunteers. This finding is different from the based on a general population of Italian participants in a previous study [ 25 ]. A possible reason for this discrepancy is that the participants whose educational background was junior college or above and those who were members of the police force always undertake more anti-epidemic duties in the community during the COVID-19 epidemic, which would increase their negative emotions and stress, resulting in poor sleep quality.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the members of the police force were more likely to report poor sleep quality than volunteers. This finding is different from the based on a general population of Italian participants in a previous study [ 25 ]. A possible reason for this discrepancy is that the participants whose educational background was junior college or above and those who were members of the police force always undertake more anti-epidemic duties in the community during the COVID-19 epidemic, which would increase their negative emotions and stress, resulting in poor sleep quality.…”
Section: Discussioncontrasting
confidence: 99%
“…Work suspension may have exposed individuals to a worsening in both physical activity and dietary habits, as also shown by Di Renzo and collaborators [21], who reported that employees who suspended work perceived an increase in weight and a change of appetite. This worsening may be justified by the abrupt disruption of daily routines but also by the economic effects of the pandemic, which arouse uncertainty about the future as well as sleep disturbances [26]. In fact, our results showed that symptoms of psychological distress perceived during lockdown were consistently associated with worsening of lifestyle.…”
Section: Discussionmentioning
confidence: 63%
“…Of these, eight were removed before screening, as duplicates. After the identification and screening phases, 11 studies [59][60][61][62][63][64][65][66][67][68][69] were included and 426 were excluded (See Flowchart, Figure 1). The number and reasons for the exclusion of the articles were the following: 7 failed to meet some inclusion criteria (six did not refer to sleep problems during the SARS-CoV-2 pandemic, one was not in English).…”
Section: Study Selectionmentioning
confidence: 99%